The Integration of Nanotechnology and Biology for Cell Engineering: Promises and Challenges - Uma Maheswari Krishnan; Swaminathan Sethuraman (Nanomaterials and Nanotechnology)
Introduction: Successful tissue engineering strategies leading to the regeneration of a tissue depend on many factors, starting from the choice of appropriate scaffold material, tailoring the surface functionalities and topography, providing the correct amount of chemical and mechanical stimuli at the appropriate time points, and ensuring the uniform and precise localization of cells. Further challenges arise when more than one cell type has to be employed for the effective regeneration of an organ. Importance: Though the use of nanomaterials has improved tissue engineering, many pitfalls still exist that present a roadblock in the translation of tissue engineering strategies to clinical practice. Apart from employing different materials with distinct surface functionalities and mechanical properties, various strategies have been employed to manipulate the surface topography and chemistry of scaffolds to create a biomimetic microenvironment for effective tissue regeneration. Conclusion: This review provides information about the factors influencing tissue engineering, namely geometry, chemistry, mechanics and cells, and the emerging concepts that may well represent the future of regenerative medicine. Electrospinning techniques and their variants, self-assembly, cell-printing techniques and cell sheet engineering, have all been elaborated in detail. These novel techniques may serve to overcome the challenges currently faced in tissue engineering.